Late onset psychosis treatment with adjunctive medicines - Boksha, Irina; Savushkina, Olga; Sheshenin, Vladimir; Tereshkina, Elena; Prokhorova, Tatyana; Pochueva, Valeriya; Burbaeva, Gulnur (Frontiers in Psychiatry, 2023)
Background -A number of studies have shown the feasibility of using complementary drugs in late onset psychosis (LOP). Aim - testing hypothesis that among LOP people treated with antipsychotics and antidepressants, basing on certain clinical characteristics a subgroup of patients might be distinguished, for whom complementary therapy is advantageous. This subgroup might be identified by measurement of blood biochemical parameters. Methods -59 in-patients with LOP, treated neuroleptics and antidepressants, were included, and followed in real clinical practice. Database containing demographic data, scores by PANSS, CDSS, CGI-S, HAMD-17, prescribed therapy, adverse effects of antipsychotic and antidepressant treatment, and blood biochemical parameters (enzymatic activities of glutamate-and glutathione metabolism enzymes in platelets and erythrocytes) at baseline and after the treatment course was created. Results -Three groups of patients (Gr1, Gr2, and Gr3), based on the adjunctive therapy usage were identified: Gr1 (n=16) was without adjunctive therapy, two other groups (Gr2 and Gr3) were with adjunctive medicines: 2-ethyl-6methyl-3-hydroxypyridine succinate (EMHS; Gr2, n=20), or other "metabolic" drugs (Gr3, n=23). Enzymatic activities were assessed also in the matched control group (n=38). In all three patient groups, as compared with controls, activity of erythrocyte glutathione reductase was decreased at baseline and after the treatment course. In Gr2, unlike Gr1 or Gr3, there was a significant decrease in baseline glutamate dehydrogenase and glutathione-S-transferase activities. Certain clinical criteria were also elucidated for prescription of EMHS as adjunctive therapy for patients of Gr2. Glutamate dehydrogenase and glutathione-S-transferase activities returned closer to control levels after the treatment course in Gr2, unlike Gr1, where they declined yet more after psychotropic treatment without adjunctive medicine. Different significant links between biochemical parameters and scores by clinical scales were observed in Gr1, Gr2, and Gr3, some having predictive value for evaluation of antipsychotic treatment efficacy.We demonstrate the validity of adjunctive neuroprotective medicines' usage in addition to antipsychotic and antidepressant therapy in distinct subgroups of patients suffering with LOP, especially those who have prominent side effects accompanying their psychotropic treatment.Returning of biochemical parameters to control range following the treatment course observed in patients of the subgroup treated with adjunctive EMHS is evidence for their metabolism normalization.